Factores de riesgo que desencadenan el síndrome de burnout del personal en la empresa privada coca cola Company en la ciudad de Tulcán. - Calpa Cuaical, Sandra Patricia (2024)
Burnout syndrome is a state of physical, emotional and mental exhaustion caused mainly by chronic stress at work, which is characterized by presenting emotional fatigue, depersonalization and a low personal accomplishment that can seriously affect health and job performance. The main objective is to identify the factors that activate the Burnout syndrome in the staff of the Coca-Cola company located in the city of Tulcan; to this purpose the methodology applied was a quantitative approach, similarly a descriptive, action field research was set, using deductive inductive, analytical-synthetic and systemic methods, which allowed to evidence the need to develop preventive educational strategies so that to reduce the risk factors of Burnout syndrome. The population of this research was made up of 60 workers, in which the Maslach Burnout Inventory (MBI) test was applied, composed of 16 questions structured in three different fields, as to mention: emotional exhaustion, depersonalization and low personal achievement. These variables were analyzed obtaining the following results: 63% presented emotional exhaustion, 55% presented depersonalization, and a significant 68% who presented low personal achievement. These results showed that the staff working in the Coca-Cola company have a medium to high level of Burnout syndrome. Thus, it can be concluded that by promoting, preventing and education strategies applied to this population, the Burnout syndrome can be prevented, consequently, it was possible to achieve wellbeing, both physical and emotional level for these workers